OZN in pravo morja - Škrk, Mirjam (Teorija in praksa, 2016)
This article analyses the role of the UN with respect to the codification and progressive development of the law of sea. This process culminated in 1982 with the adoption of the UN Convention on the Law of the Sea (UNCLOS), which entered into force in 1994, and two related agreements; namely, on Part XI and the UN fish stocks agreement. The convention regulates the entire ocean space, the use of living and non-living natural resources of the sea, navigation, protection of the marine environment against pollution, marine scientific research, and settlement of disputes regarding its interpretation and use. On the basis of the convention, new international entities have been created, such as the International Tribunal for the Law of the Sea, the International Seabed Authority, and the Commission on the Limits of the Continental Shelf. Although these bodies are independent and administered by the parties, they are closely intertwined with the UN. Thus, the UN plays a key role in managing and supervising the uses of the world oceans, including coordinating actions against piracy. However, the UN is less present, or almost not present at all, in some areas such as the South and East China Sea, the Arctic Ocean, and recently also the Mediterranean Sea with respect to solving the migrant crisis.
Keywords: arbitraža; International law; International organizations; Maritime law; Mednarodne organizacije; Mednarodno pravo; morje; OZN; Pomorsko pravo; sea